Pengembangan Media Game Edukatif KARIKA Berpendekatan Contextual Teaching and Learning untuk Meningkatkan Kemampuan Berpikir Kritis dan Kolaborasi Siswa di SMA Negeri 1 Kertek - Rifatun Hasanah; Ahmad Khoiri; Vava Imam Agus Faisal (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low level of students’ critical thinking and collaboration skills, along with the limited use of interactive learning media in physics learning, has become one of the major challenges in 21st-century education. This study aimed to develop the KARIKA educational game media based on the Contextual Teaching and Learning (CTL) approach on global warming material and to determine its validity, practicality, and effectiveness in improving students’ critical thinking and collaboration skills in grade X of SMA N 1 Kertek. This research employed the Research and Development (R&D) method using the ADDIE model, consisting of analyze, design, develop, implement, and evaluate stages. Data were collected through observation, interviews, questionnaires, tests, and documentation. The research subjects included expert validators, physics teachers, and grade X students of SMA N 1 Kertek. The results showed that the KARIKA educational game media achieved an average validity score of 91.8% categorized as “very valid”. The practicality result obtained an average score of 86.82% categorized as “very practical” based on teachers’ and students’ responses. The effectiveness of the media was indicated by the paired sample t-test results showing a significant difference before and after the implementation of the media, as well as the N-Gain results of critical thinking skills at 68.74% and collaboration skills at 59.76%, both categorized as moderate or “quite effective”. These findings indicate that the CTL-based KARIKA educational game media is feasible to be used as an innovative, interactive, and contextual physics learning medium to support the improvement of students’ critical thinking and collaboration skills.